(untitled) - Jones, Matt (New York, 2007)
Tune In is three-level listerning series for students of American English. The goal of this series is to teach students the two important aspects of listening: understanding what people say and how they say it. Teaching students to understand what people say focuses on listerning as acquisition.
Keywords: English language,Listening,Listening,Tiếng Anh thực hành,Kỹ năng nghe